Effect of receptor specificity of A/Hong Kong/1/68 (H3N2) influenza virus variants on replication and transmission in pigs. Issue 2 (4th May 2012) - Van Poucke, Sjouke; Uhlendorff, Jennifer; Wang, Zhongfang; Billiau, Veerle; Nicholls, John; Matrosovich, Mikhail; Van Reeth, Kristien
Abstract : Please cite this paper as: Van Poucke et al. (2013) Effect of receptor specificity of A/Hong Kong/1/68 (H3N2) influenza virus variants on replication and transmission in pigs. Influenza and Other Respiratory Viruses 7(2) 151–159. Background  Several arguments plead for an important role of pigs in human influenza ecology, including the similar receptor expression pattern in the respiratory tract of both species. How virus receptor binding specificity affects transmission in pigs, on the other hand, has not been studied so far. Objectives  Using recombinant viruses R1‐HK, which harbored all genes from the original pandemic virus A/Hong Kong/1/68 (H3N2), and R2‐HK, which differed by L226Q and S228G mutations in the hemagglutinin and conversion to an avian‐virus‐like receptor specificity, we assessed the role of receptor specificity on (i) replication in porcine respiratory explants, (ii) pig‐to‐pig transmission, and (iii) replication and organ tropism in pigs. Results  In nasal, tracheal, and bronchial explants, we noticed a 10‐ to 100‐fold lower replication of R2‐HK compared with R1‐HK. In the lung explants, the viruses replicated with comparable efficiency. These observations correlated with the known expression level of Siaα2, 3‐galactose in these tissues. In the pathogenesis study, virus titers in the respiratory part of the nasal mucosa, the trachea, and the bronchus were in line with the ex vivo results. R2‐HK replicated less efficiently in the lungs of pigs than R1‐HK, which contrasted with the explants results. R2‐HK also showed a pronounced tropism for the olfactory part of the nasal mucosa. Transmissibility experiments revealed that pig‐to‐pig transmission was abrogated when the virus obtained Siaα2, 3‐galactose binding preference. Conclusions  Our data suggest that Siaα2, 6‐galactose binding is required for efficient transmission in pigs.